Impalement injury to the head with intact neurology following spontaneous Dane gun explosion: Two case reports and review of the literature - Yahaya A; Koko AM (Ibom Medical Journal)
Introduction: Impalement brain injury is a complex brain trauma resulting from unusual mechanisms, especially in areas bedevilled by civil unrest.